CALCULATION OF FREE ENERGY PROTEIN MELITTIN IN MEMBRANE LIPID ON ORIENTATION DYNAMICS EFFECTS USING COARSE-GRAINED MODEL - Fachri B. Paloloang, Muhammad
Melittin is a widely studied and unique antimicrobial peptide which has a major component of bee venom but has therapeutically active agents. Melittin to perform its antimicrobial function prefer to be in certain conditions on the membrane. In this study, it simulates melittin in the horizontal orientation of the membrane surface and the vertical orientation of the transmembrane state with the condition of the peptide half structure inside and outside the membrane. Free energy is obtained by calculating the PMF at each peptide orientation to assess the least orientation showing the stable structure of this peptide interacting with the lipid bilayer. Sampling of the umbrella sampling was conducted to obtain the sampling window used in observing the free energy changes along the reaction co-ordinates. From the simulation, it was found that melittin in the vertical orientation of the transmembrane state has a smaller free energy value than the horizontal orientation, ie each of -4.01 kcal / mol and -3.98 kcal / mol which indicates that melittin is more advantageous in vertical orientation configuration. However, due to the difference in energy values in the horizontal and vertical orientation is not too large. This result assumes that this peptide will undergo a reorientation process from a vertical orientation to a horizontal orientation on the surface of the membrane to perform its antimicrobial action.